The isolation of bioactive flavonoids from Jacaranda obtusifolia H. B. K. ssp. rhombifolia (G. F. W. Meijer) Gentry - Khamsan S. (2017)
The paper describes the bioassay-guided isolation, structure elucidation and anticancer evaluation of five flavonoids (-)-liquiritigenin (1), (-)-neoliquiritin (2), isoliquiritigenin (3), isoliquiritin (4) and formononetin (5) from the twigs of Jacaranda obtusifolia H. B. K. ssp. rhombifolia (G. F. W. Meijer) Gentry. The structures were elucidated based on 1 H, 13 C NMR, comprehensive 2D NMR, MS analyses and comparison with previously reported spectral data. Compounds 1 and 3 were demonstrated to be inhibitory in vitro against NCI-H187 (small cell lung cancer) with IC 50 values of 30.1 and 16.6 μg mL -1 , respectively. The isolates were non-cytotoxic to Vero cells (African green monkey kidney).